Prática pedagógica de professores que ensinam matemática para alunos com transtorno de espectro autista - Silva, Rozélha Barbosa da (2021)
This study deepens the understanding of the importance of pedagogical practices for teaching activities, investigations of pedagogical practices in the teaching of differentiated and adaptive mathematics that contribute to the achievement of student learning.com Autism Spectrum Disorder (ASD) has been found. little information about the didactic and methodological process aimed at autistic students, currently enabling a reflection on pedagogical practices. The investigation aimed to answer the question: What are the pedagogical practices used by teachers who teach mathematics to students with ASD in the early years of elementary school. The objective of this work is to understand the pedagogical practices of teachers who teach mathematics to students with Autism Spectrum Disorder (ASD) in the Early Years of Elementary School. The work expands the understanding of pedagogical practices and inclusive practices guided by theoretical bases founded by Pimenta, Zaidan, Silva and Franco, Zabala, Montiel and Capovilla. To emphasize knowledge about teaching and learning mathematics, it will be supported by the National Curriculum Parameters (BRASIL), at BNCC; in Soares, Toledo, Silva, D’Ambrosio, Brizuela and Sandonsky. Autism Spectrum Disorder is based on the concept of reflection in recent theories by Mello, Brito, DSM-V, Carvalho and Coll, Marchesi and Palacio. Expands understanding of the term pedagogical practice by investigating a qualitative approach from Bogdan, Biklen and Creswell. In order to answer the proposed problem and reach the outlined objectives, bibliographical research was necessary to understand the object of the research, which are the pedagogical practices of two teachers from the early years of elementary school with autistic students in the classroom. The instruments used in the analysis were the semi-structured interview through e-mail questionnaires of the subjects of this research, the analysis of documents-pedagogical political project, lesson plans and medical reports of students with ASD and the activities elaborated by the subject teachers of this research. The research uses the interpretive method of documents to analyze the Locus of the Municipal School of Cuiabá Madre Marta Cerutti, and the semi-structured interview questionnaires. Points out the following result: teachers use pedagogical practices oriented in initial academic training – pedagogy – and in continuing education courses on the teaching of mathematics for the early years and Autism Spectrum Disorder. The results point to the interaction of the subjects with the approximation of the curriculum and the BNCC and seeks to understand the pedagogical practices. It concludes that reflection on pedagogical practices drives changes in the teaching of mathematics for students with ASD. The investigation consists of biases of discussions, reflections and considerations on the development and understanding of pedagogical practices for students with Autism Spectrum Disorder in public schools today. The path of the research brought an important reflection on the theme regarding pedagogical practices for the teaching of mathematics for students with ASD, fostering the need to reflectively explain the current status of special education in the State of Mato Grosso, also enabling positive views on the effectiveness of public policies of universities aimed at teacher training.